A combined DEMATEL and grey system theory approach for analyzing occupational risks: A case study in Turkish shipbuilding industry - Seker, Sukran; Recal, Fusun; Basligil, Huseyin (TAYLOR & FRANCIS INC, 2017)
The shipbuilding industry is known as heavy industry because of its high-risk work activities. Therefore, in order to prevent fatal occupational accidents in the shipbuilding industry, the processes of defining hazards, evaluating risks, taking action to eliminate or reduce risks are important issues in risk assessment. This article presents a novel occupational risk-assessment approach, which can help managers of shipbuilding make proper precautions strategies for accidents, to evaluate shipyard Critical Risk Factors and risky shipyard processes/work units. Thus, DEMATEL (Decision Making Trial and Evaluation Laboratory) and Grey system theory approaches are integrated to develop a systematic risk-assessment framework for the shipbuilding industry. This approach was applied to a real case study in a Turkish shipyard. The performance evaluation results have indicated that the combined approach can provide satisfactory risk assessment for occupational risk causes and relevant improvement strategies to prevent accidents. Sensitivity analysis was also conducted on the results to ensure the reliability of solutions. Even though a novel decision support and evaluation approach on risk implementation is introduced for shipbuilding, limitations and concerns are areas for further research opportunities. Further, a sensitivity analysis of results, managerial implications, conclusions, limitations and future research opportunities are provided.
Keywords: risk evaluation; shipyard accidents; Turkey; grey-based DEMATEL; EVALUATION LABORATORY DEMATEL; CRITICAL SUCCESS FACTORS; DECISION-MAKING TRIAL; FUZZY ENVIRONMENT; MODEL; FATALITIES; SELECTION; BARRIERS; CRITERIA; Biodiversity & Conservation; Environmental Sciences & Ecology